Strengthening Students’ Character in Akhlaq Subject Through Problem Based Learning Model - Baharun, Hasan; Ummah, Rohmatul (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2018)
This study examines the development of Akhlaq learning based on character strengthening through Problem Based Learning (PBL) model in Madrasah Aliyah Nurul Jadid, Paiton, Probolinggo. Character learning is the value engraved within a person that determines his attitude and behavior; this character can usually be shaped by education, experience, habituation, and environmental influences. Akhlaq education is an education that prioritizes the aspect of manners that always involves aspects of knowledge, feelings, and actions. Through this moral education, it is hoped to achieve a better character and can help to foster the emotional intelligence of learners in Madrasah Aliyah Nurul Jadid, Paiton, Probolinggo. The method used in this study is literary study located at Madrasah Aliyah Nurul Jadid, Paiton, Probolinggo. The results showed that Akhlaq learning through PBL approach can shape the students' thinking activities naturally and can solve the learning problem concerned with the learners’ morality. So that learners can learn about how to think critically and can be skilled in solving problems.